Relationship between knowledge management and innovation in the apple productive chain - Zanandrea, Gabriela; Camargo, Maria Emilia; Tisott, Priscila Bresolin; Dullius, Angela Isabel dos Santos (Revista de Administração da UFSM, 2020)
The constant changes which have shaped the companies environment have mobilized researchers to investigate the factors that lead them to innovate and reach higher levels of performance. In this context, knowledge management has been considered as a driving force for development and crucial for innovation. However, little attention has been paid to the use of these concepts in the agribusiness sector. Thus, this study aimed to analyze the relationship between knowledge management processes and innovation in the apple production chain in the Southern Region of Brazil from the links of production and packing-houses. For that, a quantitative, descriptive study was carried out through a survey with 166 actors of the apple production chain, whose analysis was made using the structural equation modeling technique. The results obtained provided strong support for the hypothesized relation, which showed that knowledge management significantly influences both product and process innovation. The conclusions of this study provide a theoretical and empirical basis for a better understanding of the importance of knowledge management and innovation to improve the performance of the apple production chain.